Reforms in Japan’s Private Universities - Breaden, Jeremy; Goodman, Roger (International Higher Education, 2023)
The private sector in Japan constitutes close to 80 percent of all universities, and recent debates about their governance demonstrate interesting tensions between “global” models of higher education governance and “local” practices. Key to understanding these debates is the fact that around 40 percent of Japanese private universities have been defined as what Altbach et al. have called FOMHEIs (Family-Owned or –Managed Higher Education Institutions).